Recent Advances in Return-to-work Self-efficacy Assessment Tools - LIU Feng, ZHANG Zhenxiang, MEI Yongxia, CHANG Hong, CHEN Suyan (Zhongguo quanke yixue, 2022)
Returning to work is an important sign of recovery and returning to normal life for patients. Most patients have a strong desire to return to work, however, their confidence is low. Return-to-work self-efficacy is not only a reflection of patients' confidence in returning to work but also an important predictor of his readiness to get back to work. Based on the concept and meaning of return-to-work self-efficacy, this study introduces its related theoretical models, summarizes the contents, scoring criteria, validity and reliability of related assessment tools, and conducts a comparative analysis of the tools, to provide Chinese rehabilitation care workers with evidence contributing to the selection of an appropriate return-to-work self-efficacy assessment tool.